Biological Nurturing Baby-led Feeding to Reduce the Pain Intensity of Post-Section Caesarian: A Quasi-Experimental Study - A'inurrohmah, Siti; Mukhoirotin, Mukhoirotin (Pediomaternal Nursing Journal, 2022)
Introduction: Caesarean surgery can cause pain that affects mobilization, daily activities, and the process of breastfeeding the baby. Baby-led feeding is one of the recommended breastfeeding positions for postpartum mothers post-Caesarean because it feels more relaxing. However, the effectiveness of baby-led feeding at reducing the pain levels needs further research. This study therefore aimed to determine the effect of baby-led feeding on the pain intensity among post-Caesarean section patients.Methods: The research design used was quasi-experiment with a pre-test-post-test control group design and multi-stage sampling. This totaled 26 respondents across the two groups. The biological nurturing baby-led feeding treatment was given every feeding time. The research instrument used was the Numeric Rating Scale (NRS), and the data was analyzed using a Paired Sample T-Test and an Independent Sample T-Test with α â‰¤ 0.05.Results: This study showed there to be an effect of biological nurturing baby-led feeding on the pain intensity experienced by the patients with a p-value of 0.000 (pâ‰¤0.05). There were significant differences in pain intensity between the intervention and control groups with a p-value of 0.001 (pâ‰¤0.05).Conclusion: Biological nurturing in the form of baby-led feeding is effective at reducing the pain intensity of post-Caesarean section patients. Further research recommends that post-intervention pain observations be carried out on the first day after the baby-led feeding intervention is initiated.